Mn-doped Ni-coordination supramolecular networks for binder-free high-performance supercapacitor electrode material. (20th October 2019) - Li, Qiujun; Yao, Hua; Liu, Feng; Gao, Zitao; Yang, Yangyi
Abstract: A new Mn-doped coordination supramolecular network (CSN) was synthesized on nickel foam directly by a simple one-step hydrothermal method. Compared with the pure CSN electrode (∼2.46 C cm −2 at 10 mA cm −2 ), this Mn-doped binder-free electrode showed an ultrahigh areal capacity (∼8.12 C cm −2 at 10 mA cm −2 ). In addition, when the current density increased from 10 mA cm −2 to 50 mA cm −2, it had a good rate capability with 73.33% capacitance retention. For practicality, an asymmetrical supercapacitor (ASC) was assembled by Activated Carbon (AC) electrode and the Mn-doped CSN electrode. The device not only could achieve a maximum energy density of 3.41 mW h cm −3 at the power density of 44.98 mW cm −3, but also could exhibit excellent stability after 4000 cycles, with the capacitance retention of 90.14%. The above results indicate that the Mn-doped CSNs are promising electrode materials for supercapacitors in energy storage.